2005
DOI: 10.1007/s00127-005-0842-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of severe mental illness, co-morbid personality disorders and demographic factors on psychiatric bed use

Abstract: Psychosis, personality disorder and unemployment appear to have independent effects on psychiatric bed use. Patients with a combination of psychotic disorders and diffuse personality disorders were very high users of inpatient services. This suggests that this group have particular needs that community mental health teams find difficult to manage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Additionally, only principal diagnoses, not comorbid illnesses, were analysed. In previous studies, the influence of psychiatric comorbidity on patients with mental illnesses was inconsistent [18,69,70], but comorbid physical illnesses prolonged LOS of psychiatric patients [71][72][73]. In the present study, however, preliminary analyses showed that comorbidities differently affected to each principal diagnosis.…”
Section: Limitationscontrasting
confidence: 75%
“…Additionally, only principal diagnoses, not comorbid illnesses, were analysed. In previous studies, the influence of psychiatric comorbidity on patients with mental illnesses was inconsistent [18,69,70], but comorbid physical illnesses prolonged LOS of psychiatric patients [71][72][73]. In the present study, however, preliminary analyses showed that comorbidities differently affected to each principal diagnosis.…”
Section: Limitationscontrasting
confidence: 75%
“…Ethnicity has been found to have no effect on LOS [11, 29], though Tulloch et al [11] found a significant effect of ethnicity that was found not to be independent of other effects. In the present study, Asian or Asian British, Black or Black British, and Mixed background ethnicity categories were associated with a longer LOS than White or White British recorded ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…116,117 Many previous studies of the excess detention of BME patients have been from London, which may not be representative of other areas of the UK. A large study of 22 psychiatric hospitals in England found no association between ethnicity and patient perceptions of coercion at admission or during the first 4 weeks of inpatient stay.…”
Section: Discussionmentioning
confidence: 99%